Embezzlement and Guilt Aversion - Giuseppe Attanasi; Claire Rimbaud; Marie Claire Villeval (Institute of Labor Economics (IZA), 2018)
Psychological game theory can contribute to renew the analysis of unethical behavior by providing insights on the nature of the moral costs of dishonesty. We investigate the moral costs of embezzlement in situations where donors need intermediaries to transfer their donations to recipients and where donations can be embezzled before they reach the recipients. We design a novel three-player Embezzlement Mini-Game to study whether intermediaries in the laboratory suffer from guilt aversion and whether guilt aversion affects the decision to embezzle. We show that the proportion of guilt-averse intermediaries is the same irrespective of the direction of guilt and guilt aversion reduces embezzlement. Structural estimates indicate no difference in the effect of guilt aversion toward the donor and toward the recipient on intermediaries' behavior. This is striking as embezzlement affects the earnings of the recipient but not those of the donor. It shows that guilt aversion matters even when decisions have no direct monetary consequences.
Keywords: C91; 330; embezzlement; dishonesty; guilt aversion; psychological game theory; experiment